The implications of laboratory Rn-222 flux measurements to the radioactivity in groundwaters: the case of a karstic limestone aquifer - Bonotto, Daniel Marcos [UNESP]; Andrews, J. N. (Elsevier B.V., 1997)
Laboratory time-scale experiments were conducted on Carboniferous Limestone gravels from the Mendip Hills area, England, with the purpose of evaluating the release of Rn-222 to the water phase. The specific surface areas of the samples were 4.14 and 1.69 cm g(-1), which provided, respectively, values of 50.6 and 12.7 pCi for the released Rn. These results allowed the calculation of the emanation coefficient of this rock matrix with respect to the release of Rn, where completely different values corresponding to 23% and 6% were found, suggesting that the extent to which grain boundaries or imperfections in aggregates of micro-crystals of calcite intersect the particle surface certainly affects the Rn release. They also permitted the evaluation of models for the generation of Rn in rocks and transfer to water, in order to interpret the radioactivity due to this gas in groundwaters from the karstic aquifer of the Mendip Hills area, where the calculated activities in groundwater based on the values of 23% and 6% for the emanation coefficient were about 51 and 15 times higher than actually measured in groundwater. Therefore, the emanation coefficient in nature is considerably smaller than in the lab experiment, and another factor k (0 < k < 1) may be introduced into the equations related to the modelling, with the aim of adjusting the theoretical-practical results. (C) 1997 Elsevier B.V. Ltd. All rights reserved.